Mobile technologies in children's language and literacy : innovative pedagogy in preschool and primary education - Oakley, Grace (Emerald Publishing Limited, 2018)
Mobile technologies can facilitate different kinds of learning, ina range of contexts. They can also enable innovative and powerful ways ofparticipating in collaborative learning. This book examines the ways in whichmobile technologies may contribute to, change, or disrupt literacy learning inchildren up to the age of twelve. Also explored is the impact mobiletechnologies may have on literacy definitions and practices; learningenvironments; student, parent and teacher roles and interactions; powerrelations in education; and social and material interactions. Contributing authors include eminent researchers and innovative practitioners from around the world, who share their insights on the possible roles of mobile technologies in literacy practices and education. This book explores how educators might harness mobile technologies toequip literacy learners for the 21th century, as well as considering how mobile technologies may help toenhance access to quality literacy education for children in developing countries.